Noli me tangere Episodes 1 to 13 TV series in DVD - Arago, Jorge; Romero, Eddie; Ruiz, Ruby.; Tinio, Rolando; Tiongson, Nicanor; Cultural Center of the Philippines (Manila Cultural Center of the Philippines, 1992)
An adaptation of the novel of Dr. Jose Rizal on Philippine nationalism. This television series exposes the abusive powers of the Spanish rulers in the Philippines, in particular the Spanish priests.
Disc 1. Episode 1: Crisostomo Ibarra (45 min.), Episode 2: Sisa (45 min.), Episode 3: Dito po sa amin (45 min.) -- Disc 2. Episode 4: Ang baliw ay pantas (45 min.), Episode 5: Nagdidilim ang langit (45 min.), Episode 6: Haka-haka at kuro-kuro (45 min.) -- Disc 3. Episode 7: Kaibigang lihim (45 min.), Episode 8: Katuwiran at kapangyarihan (45 min.), Episode 9: Pagbubunyag (45 min.) -- Disc 4. Episode 10: Bayan o sarili (45 min.), Episode 11: Ama ng ikakasal (45 min.) -- Disc 5. Episode 12: Noche Buena (53 min.), Episode 13: Pasko (10 min.)
Boxed set includes 5 DVDs containing 13 episodes.
Based on the novel written by Jose P. Rizal.
Executive producer, Ruby Ruiz ; isinalin sa Pilipino nina Jorge Arago, Nicanor Tiongson, Rolando Tinio ; cinematography, Nap Jamir.
Joel Torre, Maria Jose Arnaldo
In Tagalog.
Keywords: Rizal, Jose -- 1861-1896. -- Film and video adaptations; Fiction television programs